B-Site modification of LaMn0.9Co0.1O3 perovskite using a selective dissolution method in C3H6 oxidation. Issue 19 (23rd September 2020) - Liu, Zhan; Li, Zhengguo; Chu, Xuefeng; Shao, Yuankai; Li, Kaixiang; Chen, Xiaoping; Liu, Haiyan; Chen, Jianjun; Li, Junhua
Abstract : LaMnCoO3 is treated with HNO3 to generate a Co-doped MnO2 phase, which shows better catalytic performance than LaMnO3 and pure MnO2 catalysts for C3 H6 oxidation. Abstract : A Co-doped MnO2 catalyst with a trace amount of Co was synthesized by a selective dissolution method using LaMn0.9 Co0.1 O3 as a perovskite precursor. The obtained catalyst exhibited much higher catalytic activity than pure LaMn0.9 Co0.1 O3 and MnO2 with excellent selectivity to CO2 and resistance to H2 O in the range of 90–350 °C. Its superior performance was induced by the surface reducibility, surface-active oxygen, and the synergistic effect between the trace amount of Co and MnO2 .